Study on the Influence of the Blasting of Preceding Tunnel on the Pre-Penetration Surrounding Rock in Succeeding Tunnel with Small Clear Distance. (1st August 2022) - Bao, Xiankai; Zhang, Wu; Zhao, Shuang; Yu, Chaoyun; Lü, Yongjun; Wang, Shurui; Wu, Ning
Abstract : To study the influence of the preceding tunnel blasting on the surrounding rock in the pre-penetration area of the succeeding tunnel, combined with the actual monitoring of the Kaifeng Mountain small clear distance tunnel, the relationship between the vibration velocity and the blasting center distance was derived according to the energy attenuation law, predicted the peak velocity of particle vibration on the pre-penetration surrounding rock, came up with the conception of surrounding rock seismic wave vibration velocity ratio, obtained its change situation, and then established a numerical model to further analyze the changes in vibration velocity, plastic strain, and stress. The results show the prediction formula of peak vibration velocity obtained from theoretical analysis of vibration velocity, which can well calculate the peak vibration velocity of some unmeasurable points in tunnel engineering and provide theoretical support for actual tunnel blasting engineering. Under the same clear distance conditions, the front blasting side of surrounding rock in the pre-penetration area of the succeeding tunnel is affected by blasting vibration more than the back blasting side, and the vibration velocity decreases gradually from the arch waist⟶arch shoulder⟶arch foot⟶vault (arch bottom), and the most unfavorable section is that the blasting surface is parallel to the surrounding rock section in the pre-penetration area of the preceding tunnel. The excavation of the lower step has greater destructive force than that of the upper step; with the clear distance that gradually increases, the impact of the preceding tunnel blasting on the surrounding rock in the pre-penetration area of the succeeding tunnel becomes smaller, and D (D is the tunnel span) is the minimum safe clear distance.